Reading Islamophobia in education policy through a lens of critical race theory: a study of the 'funding freeze' for private Islamic schools in Australia. Issue 1 (2nd January 2020) - Rowe, Emma
ABSTRACT: This paper draws on critical race theory to explore the reproduction and enactment of Islamophobia in education policy. It will focus on an unprecedented policy intervention in which the federal Australian government withdrew funding from the largest Islamic private schools in the country. Australia represents a useful context to explore intersections between Islamophobia and the education market; as a diverse country which ardently supports religious protections, it maintains a well-subsidised private school sector, larger than comparable OECD countries. Thus, it is the first incident in Australian public policy in which a private school has had their funding formally withdrawn reportedly due to 'non-compliance' and 'misalignment with Australian values'. This paper focuses on the media reporting of the incident, illuminating consistently negative tropes utilised in relation to Islamic schools. The contradictions of muscular liberalism and secularism are explicated in critical exclusions of Islamic schools and cultural practices, as couched in whiteness.